1994
DOI: 10.2466/pr0.1994.75.1.651
|View full text |Cite
|
Sign up to set email alerts
|

Theory, Development, and Interpretation of the CPI Socialization Scale

Abstract: The socialization (So) scale of the California Psychological Inventory is based partly on a role-taking or perspective-taking theory of social deviance and partly on the pragmatics of differentiating between more socialized and less socialized individuals. The theory, history, and current applications of the scale are reviewed, relationships to other scales and measures are examined, and the validity of the scale in arraying 69 male and 40 female samples along a putative continuum of socialization is evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 115 publications
2
107
3
Order By: Relevance
“…Dikman et al (2001), in an analysis of the subjects reported in Dikman and Allen (2000), found that the correlation between RSA and defensiveness was significant (r = −.41, P < .05) in a sample of 34 college students. This relationship was not moderated by gender, nor by participant's socialization status as defined by the socialization scale of the California Psychological Inventory (Gough, 1994).…”
Section: Vagal Tone and Defensivenessmentioning
confidence: 76%
“…Dikman et al (2001), in an analysis of the subjects reported in Dikman and Allen (2000), found that the correlation between RSA and defensiveness was significant (r = −.41, P < .05) in a sample of 34 college students. This relationship was not moderated by gender, nor by participant's socialization status as defined by the socialization scale of the California Psychological Inventory (Gough, 1994).…”
Section: Vagal Tone and Defensivenessmentioning
confidence: 76%
“…To eliminate overlap with assessing IPV, the irritability and aggressiveness criterion was not included in the APD total. Other measures of female antisociality/generalized violence were the socialization scale of the California Personality Inventory (Gough, 1994) and the physical aggression scale from the Buss-Durkee Aggression Questionnaire (Buss and Perry, 1992). Finally, the General Violence Confl ict Tactics Scale (Stuart et al, 2006) was used to assess past-6-month physical assault frequency toward nonpartners, and this scale was inversely transformed within the models to reduce skewness.…”
Section: Methodsmentioning
confidence: 99%
“…These subjects were older than the subjects tested by Moss and colleagues, and they were tested on both a day of stress and a day of rest to obtain a well-defined basal cortisol secretion pattern. The subjects were classified as to antisocial tendencies using the Sociability Scale of the California Personality Inventory (Gough, 1994;Kosson et al, 1994). The subgroup that was FH+ and low in sociability had a significantly attenuated stress cortisol response.…”
Section: Altered Hpa Stress Reactivity In Persons At Risk For Addictionmentioning
confidence: 99%